A Passive Polycentric Mechanism to Improve Active Mediolateral Balance in Prosthetic Walking - Evert S. van Hal; Juha M. Hijmans; Klaas Postema; Egbert Otten (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2024)
Prosthetic legs are typically passive systems without active ankle control, restricting mediolateral balancing to a hip strategy. Resulting balance control impairments for persons with a lower extremity amputation may be mitigated by increasing hip strategy effectiveness, in which relatively small hip moments of force are adequate for mediolateral balancing. To increase hip strategy effectiveness we have developed a prosthetic leg prototype based on the Peaucellier mechanism, the Sideways Balance Mechanism (SBM). This polycentric mechanism adds a frontal plane degree of freedom, reducing mediolateral body displacements. Adding a passive joint alone introduces instability, in which mediolateral body rotation leads to CoM height loss, ultimately resulting in a fall. The SBM however provides stability typically absent by lengthening under rotation, thereby compensating for CoM height loss. By allowing for both foot rotation (in-/eversion), and increased mediolateral ground reaction force the SBM increases hip strategy effectiveness. We aimed to provide proof of principle that the SBM can improve active mediolateral balance control in prosthetic walking by increasing hip strategy effectiveness compared to a typical set-up. Comparison between a typical set-up and the SBM showed an increased mediolateral ground reaction force at equal hip moments of force for a 2D forwards dynamics computer simulation, and a reduced hip moment of force at equal mediolateral ground reaction force for a case study. Results validate increased hip strategy effectiveness of the SBM compared to a typical set-up, providing proof of principle that adding an SBM to a prosthetic set-up improves mediolateral balance control in prosthetic walking.